Molecular characterization of poultry red mite, Dermanyssus gallinae lineages in Turkey and first report of Plasmodium species in the mite populations. Issue 4 (18th May 2020) - Ciloglu, Arif; Yildirim, Alparslan; Onder, Zuhal; Yetismis, Gamze; Duzlu, Onder; Simsek, Emrah; Inci, Abdullah
ABSTRACT: Dermanyssus gallinae:, the poultry red mite is an obligatory blood-sucking ectoparasite and has been involved in the transmission of several pathogens between both animals and humans. In order to develop effective control strategies against D. gallinae, it is essential to determine their genetic compositions and investigate the potential vector roles of these mites. Therefore, we aimed to analyse the mt-COI gene regions of D. gallinae populations and investigate avian haemosporidian parasites in order to point out their risk potentials for the presence of possible transmission by these mites. In total, 1985 mites were collected from five laying hen breeding facilities in Central Anatolia Region in Turkey. The mt-COI sequence analyses of 100 individual mites identified 6 haplotypes (TD1 to TD6) in three haplogroups. Although the local lineages are common in the region, our findings also support the possibility of international transmission of D. gallinae . A total of 126 pools of D. gallinae were screened for investigation of three genera of avian haemosporidians. In total, five pools from three facilities were identified as positive for species of Plasmodium . These findings provide novel molecular data on the possible vector role of D. gallinae in the transmission of avian haemosporidians and draw attention to the risk potentials in poultry farms.